Assessment of prevalence, predictors, reasons and regulations of substance smoking among children in Ghana - Sylvester Kyei-Gyamfi; Frank Kyei-Arthur (BMC, 2023)
Abstract Background In Ghana, it is against the law for children to smoke. Nevertheless, a portion of children in the country do smoke. However, there is a paucity of research on young smokers in Ghana and other sub-Saharan African nations. This study, therefore, investigated the prevalence of smoking, the kinds of substances children smoke, predictors of smoking, reasons for and factors that lead children to smoke, and regulation of smoking among children in Ghana. Methods In total, 5024 children aged 8-17 were studied using a cross-sectional convergent parallel mixed method. Descriptive statistics, Person's Chi-square test, Fisher Exact test, and binary logistic regression were used to analyse the quantitative data. In contrast, thematic analysis was used to analyse the qualitative data. Results The results showed that 3.2% of children had ever smoked. Male children smoked more often than female children. The prevalence of cigarette, marijuana, and shisha smoking was 78.3%, 18%, and 3.7%, respectively. While more male children than female children smoked cigarettes and marijuana, more female children than male children used shisha. Children mainly smoked for fun and due to group culture. In addition, children were influenced by friends; parents, family members, and neighbours who smoke; curiosity; and advertisements and videos to initiate smoking. Despite the availability of regulations and laws regulating tobacco products in public places, tobacco advertisement, promotion, and sale to persons under 18, children are still smoking. Conclusions Children who have ever engaged in smoking reported using cigarettes, marijuana, and shisha. Policymakers urgently need to strategise and strengthen their policies, programmes, and interventions to address smoking among children.